Free testosterone level in patients with homozygous beta thalassemia on regular transfusions regimen - Riadi Wirawan; Elly Santosa; Lyana Setiawan; Bulan Ginting Munthe; Dalima AW Astrawinata (Paediatrica Indonesiana, 2004)
Background Patients with homozygous beta thalassemia requireregular transfusions which will lead to iron deposition in tissuesincluding testicles.Objective This study aimed to evaluate testicular function in syn-thesizing testosterone by measuring free testosterone level. Thecorrelation between free testosterone level and transferrin satura-tion was evaluated.Methods This was a cross sectional study. Sampling was doneconsecutively. Free testosterone level was measured by radioim-munoassay in 20 homozygous beta thalassemic patients receiv-ing regular transfusions and compared to 20 healthy subjects.Results Fourteen out of 20 patients showed free testosterone levelbelow the reference range. Out of 20 thalassemic patients, onepatient’s serum was not enough for transferrin saturation determi-nation. Among the 19 patients, 18 had transferrin saturation above55%, 1 less than 55%, while all healthy subjects had normal trans-ferrin saturation. A significant difference was found between thetwo groups, both in the free testosterone level (p=0.001) and trans-ferrin saturation (p<0.001). A very weak correlation was found be-tween free testosterone level and transferrin saturation (r=-0.215).Conclusion We concluded that there might be a relationship be-tween iron overload and testicular endocrine function in patientswith homozygous beta thalassemia receiving regular transfusions